Mental Wellbeing of Family Members of Autistic Adults - Herrema, Renske (J Autism Dev Disord, 2017)
Family members are often the primary caregiver for autistic adults and this responsibility may impact on the carer’s wellbeing and quality of life. 109 family members of autistic adults completed an online survey assessing their wellbeing relating to their caring role for their autistic relative. Family members who were supporting an autistic relative with co-occurring mental health difficulties and who they reported as unprepared for the future, self-reported higher levels of worry, depression, anxiety and stress, and poorer quality of life. These findings emphasise the importance of support for family members of autistic adults, whether through external services to support their relative or individual mental health support for the carer.